A multicenter, retrospective study of cardiac disease in Borzoi dogs - Sykes, K. Tess; Wesselowski, Sonya; Saunders, Ashley B.; Tjostheim, Sonja S.; Potter, Brianna M.; Gelzer, Anna R. M.; Katz, Natalie; Ward, Jessica L.; Karlin, Emily T.; Markovic, Lauren E.; Magee, Aliya N.; Abbott, Jonathan A.; et al. (Frontiers in Veterinary Science, 2023)
Borzoi are large, relatively uncommon sighthounds anecdotally reported to suffer from sudden death. This multicenter retrospective cohort study aimed to describe the sample of Borzoi presenting to veterinary cardiologists for evaluation, with records searched from 14 centers across a study period of up to 20 years. The study sample was comprised of 152 client-owned Borzoi, with dogs most commonly presenting for pre-breed screening in 87/152 (52%), followed by evaluation of an arrhythmia in 28/152 (18%). Of the 131/152 (86%) dogs that had an echocardiogram performed, 85/131 (65%) were structurally normal, with 40/85 (47%) structurally normal dogs having trace or mild atrioventricular valve regurgitation. Tricuspid valve dysplasia was the most commonly diagnosed congenital cardiac disease (n=6). Myxomatous mitral valve disease (n=12) and dilated cardiomyopathy (n=13) were diagnosed at similar frequencies, though 92% of valve disease cases were mild. Only 48/152 (32%) Borzoi had a diagnostic electrocardiogram (ECG) and/or a Holter monitor for arrhythmia screening. Despite this, ventricular arrhythmias were identified during the entirety of the available cardiac evaluation including diagnostic ECG, contemporaneous ECG monitoring during the echocardiogram, and/or Holter monitor in 25/131 (19%) dogs in which an echocardiographic diagnosis was available. Of these 25 Borzoi, 76% had minimal or no structural cardiac disease identified, and five had a family history of sudden death. A sudden death outcome was reported in 3/55 (5%) Borzoi with long-term outcome data available. In conclusion, Borzoi commonly have trace or mild atrioventricular valve insufficiencies, and may develop ventricular arrhythmias and dilated cardiomyopathy.